Structure of interfaces in layered ferroelectrics of first and/or second order transition - Chew, Khian Hooi; Shin, F.G.; Tsang, C.H.; Ishibashi, Y. (2004)
We studied the structure of interfaces in layered ferroelectrics comprising two different ferroelectric materials with first and/or second order transitions. The layered structure is described using the Landau-Ginzburg theory by including a bilinear coupling at the interface between the two neighboring layers. The interfacial coupling leads to the variation of polarization across the interface from one layer to another. An abrupt or continuous change of polarization across the interface is found to depend on the strength of coupling. For a layered structure having a layer in paraelectric phase, an interface-ordered state is predicted (in the paraelectric layer) as a manifestation of interfacial coupling. The Tilley-Zeks model is compared with the present approach to discuss the relationship between the bilinear coupling parameter and the extrapolation lengths.